Structural insights of human mitofusin-2 into mitochondrial fusion and CMT2A onset - Li, Yu-Jie; Cao, Yu-Lu; Feng, Jian-Xiong; Qi, Yuanbo; Meng, Shuxia; Yang, Jie-Feng; Zhong, Ya-Ting; Kang, Sisi; Chen, Xiaoxue; Lan, Lan; Luo, Li; Yu, Bing; et al. (Nature communications, 2019)
Mitofusin-2 (MFN2) is a dynamin-like GTPase that plays a central role in regulating mitochondrial fusion and cell metabolism. Mutations in MFN2 cause the neurodegenerative disease Charcot-Marie-Tooth type 2A (CMT2A). The molecular basis underlying the physiological and pathological relevance of MFN2 is unclear. Here, we present crystal structures of truncated human MFN2 in different nucleotide-loading states. Unlike other dynamin superfamily members including MFN1, MFN2 forms sustained dimers even after GTP hydrolysis via the GTPase domain (G) interface, which accounts for its high membrane-tethering efficiency. The biochemical discrepancy between human MFN2 and MFN1 largely derives from a primate-only single amino acid variance. MFN2 and MFN1 can form heterodimers via the G interface in a nucleotide-dependent manner. CMT2A-related mutations, mapping to different functional zones of MFN2, lead to changes in GTP hydrolysis and homo/hetero-association ability. Our study provides fundamental insight into how mitofusins mediate mitochondrial fusion and the ways their disruptions cause disease. Mitofusin-2 (MFN2) is a dynamin-like GTPase that plays a central role in regulating mitochondrial fusion and cell metabolism. Here, authors report crystal structures of truncated human MFN2 in different nucleotide-loading states and show that MFN2 forms sustained dimers even after GTP hydrolysis.